Preparation method of A-type molecular sieve as well as product and application of A-type molecular sieve

Through the calcination of aluminum ash and alkaline compounds and the treatment of white carbon black, the silicon-aluminum molar ratio was controlled, and A-type molecular sieve with excellent adsorption performance was solved, which solved the problem of insufficient preparation performance of aluminum ash treatment and A-type molecular sieve, and achieved high efficiency adsorption properties and calcium ion exchange amount.

CN119191314APending Publication Date: 2024-12-27BENGBU COLLEGE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307427.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat and utilize aluminum ash, resulting in waste of resources and environmental pollution, and at the same time, it is unable to provide an effective preparation method for type A molecular sieve to improve its adsorption performance.

Method used

By mixing aluminum ash with alkaline compounds and heating and calcining, combining the treatment of white carbon black and alkaline compounds, the silicon-aluminum molar ratio is controlled to 1.6-2.0, especially 1.8, and heating crystallization, washing, filtration and drying, to prepare A type A molecular sieve with excellent adsorption properties was obtained.

Benefits of technology

It improves the degree of crystal structure perfection, adsorption performance and calcium ion exchange of type A molecular sieve, reduces the generation of heterogeneous crystals, enhances the uniformity of pore size distribution and morphological regularity, and is suitable for the field of adsorption or separation technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049675710000141
    Figure BDA0005049675710000141
  • Figure BDA0005049675710000171
    Figure BDA0005049675710000171
  • Figure HDA0005049675720000011
    Figure HDA0005049675720000011
Patent Text Reader

Abstract

The invention relates to the technical field of molecular sieves, in particular to a preparation method of an A-type molecular sieve as well as a product and application thereof. The preparation method of the A-type molecular sieve comprises the following steps: S1, mixing aluminum ash and an alkaline compound, and heating to obtain a treated substance a; s2, white carbon black and an alkaline compound are mixed, and a treated substance b is obtained; s3, mixing the treated substance a and the treated substance b to obtain a mixture c, and heating, crystallizing, washing, filtering and drying the mixture c to obtain the A-type molecular sieve, the treated material a and the treated material b are respectively mixed with water and then are mixed to obtain a mixture c. According to the preparation method provided by the invention, the crystal structure perfection degree of the A-type molecular sieve can be improved, the adsorption performance of the A-type molecular sieve is improved, and the calcium ion exchange capacity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of molecular sieves, and in particular to a preparation method of type A molecular sieves, products thereof and applications. Background Art

[0002] Type A molecular sieve is a microporous material of aluminosilicate with a pore structure. At present, there are related technologies to modify aluminum to obtain type A molecular sieve; aluminum ash is a hazardous solid waste generated during the aluminum processing and recycling process, also known as "black ash", and its aluminum content is about 10% to 20%; with the development of industrial technology, my country produces at least millions of tons of aluminum ash every year, but for the treatment of aluminum ash, direct landfill is generally used, which not only causes a waste of resources, but also brings hidden dangers to land and environmental safety. The country also attaches great importance to industrial environmental protection issues. Therefore, the treatment of aluminum ash is also extremely important, and it is also important to reuse it after treatment.

[0003] A Chinese patent with patent publication number CN101693542A discloses a method for producing a 4A molecular sieve using high-aluminum fly ash, but the processing process is complicated and no solution is provided for the effect of the heating crystallization process on the crystal form in the molecular sieve.

[0004] Therefore, providing a type A molecular sieve with excellent adsorption performance prepared using aluminum ash as raw material is the main technical problem that needs to be solved at present. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing type A molecular sieve, comprising the following steps:

[0006] S1. The aluminum ash and the alkaline compound are mixed and then heated to obtain a treated product a;

[0007] S2. The white carbon black and the alkaline compound are mixed to obtain a treated material b;

[0008] S3. The treated material a and the treated material b are mixed to obtain a mixture c, and the mixture c is heated for crystallization, washed, filtered, and dried to obtain a type A molecular sieve;

[0009] The treated product a and the treated product b are mixed with water respectively and then mixed to obtain a mixture c.

[0010] In one embodiment, the treatment product a is mixed with water without being limited to a specific step, and can be obtained in S1 or in S3.

[0011] In one embodiment, the treatment product b is mixed with water without being limited to a specific step, and can be obtained in S2 or in S3.

[0012] In one embodiment, in S1, the aluminum ash is first washed with water to obtain desalted aluminum ash.

[0013] In one embodiment, the mass ratio of the desalted aluminum ash to the alkaline compound in S1 is 1:(1.5-2.5).

[0014] In one embodiment, after the desalted aluminum ash and the alkaline compound in S1 are mixed, the temperature is raised to 600° C. and calcined for 100-150 min to obtain a treated product a.

[0015] In a preferred embodiment, the desalted aluminum ash and the alkaline compound in S1 are mixed, heated to 600° C., and calcined for 120 min to obtain a treated product a.

[0016] In one embodiment, the alkaline compound in S1 is sodium hydroxide.

[0017] In one embodiment, after the desalted aluminum ash and the alkaline compound are mixed in S1, they are heated to 600°C at a heating rate of 1-10°C / min.

[0018] In one embodiment, the heating temperature rise rate in S1 includes but is not limited to 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min.

[0019] In one embodiment, the treated material a is leached with water, kept at 40-70° C. for 20-50 min, and then filtered to obtain a sodium aluminate solution.

[0020] In one embodiment, the alkaline compound in S2 is sodium hydroxide.

[0021] In one embodiment, the treated material b is dissolved in water to obtain a sodium silicate solution, and the sodium silicate solution is then mixed with a sodium aluminate solution.

[0022] In one embodiment, when the treated material b and the treated material a are mixed in S3, the silicon-aluminum molar ratio is 1.6-2.0.

[0023] In one embodiment, when the treated material b and the treated material a are mixed in S3, the silicon-aluminum molar ratio is 1.8-2.0.

[0024] In a preferred embodiment, when the treated material b and the treated material a are mixed in S3, the silicon-aluminum molar ratio is 1.8.

[0025] In order to improve the crystal structure perfection of type A molecular sieve, improve the adsorption performance of type A molecular sieve, and improve the calcium ion exchange capacity, the inventor found in the experiment that the above problems can be solved when the silicon-aluminum mole ratio is controlled at 1.6-2.0, particularly when the silicon-aluminum mole ratio is 1.8, the inventor found in the experiment that the change of its silicon-aluminum mole ratio when sodium silicate solution and sodium aluminate solution are mixed, the crystallinity and crystal structure of type A molecular sieve obtained also have a significant impact. When the silicon-aluminum mole ratio is 1.4, it can be observed that the crystallinity of type A molecular sieve is also at a relatively low level, and the crystal structure of type A molecular sieve is not quite perfect. With the gradual improvement of silicon-aluminum mole ratio, type A molecular sieve has good adsorption performance, improves calcium ion exchange capacity, and the possible reason is that the gradual improvement of silicon-aluminum mole ratio can promote the speed of its nucleus formation and the growth efficiency of crystals in the preparation process of type A molecular sieve. During the experiment, the inventors found that when the silicon-aluminum molar ratio increased from 1.4 to 1.8, type A molecular sieve crystals began to form, so that type A molecular sieve had good adsorption performance; when the silicon-aluminum molar ratio exceeded 2.0, the crystal structure of type A molecular sieve changed, and the growth rate of the crystal began to exceed the nucleation rate, resulting in an increase in the crystal volume. The structure of type A molecular sieve gradually changed, resulting in a weakened adsorption capacity of the molecular sieve for calcium ions.

[0026] S3. The treated product a and the treated product b are mixed to obtain a mixture c, and the mixture c is heated for crystallization, washed, filtered, and dried to obtain a type A molecular sieve.

[0027] In a preferred embodiment, in S3, the sodium aluminate solution and the sodium silicate solution are mixed to obtain a mixture c, and the mixture c is heated for crystallization, washed, filtered, and dried to obtain a type A molecular sieve.

[0028] In one embodiment, when the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.6-2.0.

[0029] In a preferred embodiment, when the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0030] In one embodiment, the method for preparing the type A molecular sieve comprises the following steps:

[0031] S1. The aluminum ash is washed with water to obtain desalted aluminum ash, the desalted aluminum ash is mixed with an alkaline compound, and then heated to 600°C, and calcined for 100-150min to obtain a treated product a, wherein the heating rate is 1-10°C / min;

[0032] S2. Mixing white carbon black and an alkaline compound to obtain a treated product b; S3. Mixing a sodium aluminate solution and a sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve;

[0033] The treated material a is leached with water, kept at 40-70° C. for 20-50 minutes, and then filtered to obtain a sodium aluminate solution;

[0034] The treated material b is dissolved in water to obtain a sodium silicate solution.

[0035] In one embodiment, in S1, aluminum ash is added to deionized water, and washed with water at 40°C with continuous stirring for 2 hours. After washing, the aluminum ash is filtered and dried to obtain desalted aluminum ash. The desalted aluminum ash is mixed with an alkaline compound, heated to 600°C, and calcined for 100-150 minutes to obtain a treated product a, and the heating rate is 1-10°C / min;

[0036] In one embodiment, the temperature of the heating crystallization in S3 is 90-100°C.

[0037] In a preferred embodiment, the temperature of the heating crystallization in S3 is 100°C.

[0038] In order to reduce the generation of impurity crystals in type A molecular sieve and improve the adsorption performance of type A molecular sieve, the inventors found in the experiment that controlling the temperature of heating crystallization to 90-100°C can solve the above problems; the inventors found in the experiment that a higher crystallization temperature will lead to an accelerated growth rate of molecular sieve crystals. When the crystallization temperature increases, the amorphous gel formed by mixture c will catalyze the formation of sodium aluminosilicate anion skeleton; when the crystallization temperature is 80°C, the crystal structure is incomplete and the peak shape is unclear. When the crystallization temperature reaches 110°C, the crystallization speed will be too fast, and the crystal form of type A molecular sieve will change to produce impurity crystals. When the crystallization temperature exceeds 100°C or is lower than 90°C, the peak shape of the obtained type A molecular sieve is not obvious. When the crystallization temperature is 100°C, the peak shape of type A molecular sieve is clear and the skeleton grows intact. When the crystallization temperature exceeds 110°C, the adsorption capacity of the molecular sieve for calcium ions is weakened to below 325. The possible reason is the twinning phenomenon between crystals during the crystallization process, which causes the molecular sieve to undergo a dissolution-recrystallization process, thereby affecting the crystallinity and morphology, and is accompanied by the formation of impurity crystals.

[0039] In one embodiment, the heating crystallization time in S3 is 9-10 hours.

[0040] In a preferred embodiment, the heating crystallization time in S3 is 10 hours.

[0041] In order to improve the morphology regularity of type A molecular sieve, improve the calcium ion exchange capacity, the inventor found in the experiment that when the time of controlling the heating crystallization is 9-10h, the above-mentioned technical problems can be solved, when the crystallization time is long, the morphology regularity of type A molecular sieve will be affected, and the possible reason is that the increase of the crystallization time prolongs the reaction time, which will cause the reduction of the molecular sieve particle size, and the reaction time is too long to be conducive to the formation of a type A molecular sieve with good dispersibility and regular morphology. When the crystallization time is 8h, the crystallization is insufficient, and the crystal grain is small, and the crystal structure of the type A molecular sieve obtained is also incomplete and not fully formed. When the crystallization time is 10h, complete crystals can be obtained, but when the crystallization time reaches 11h, the structure of the molecular sieve crystal will change again, gradually changing to a stable state, that is, the crystals gather together to generate impurity crystals.

[0042] A type A molecular sieve is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0043] A type A molecular sieve is used in the field of adsorption or separation technology.

[0044] In order to improve the pore size and distribution uniformity of type A molecular sieve, increase the calcium ion exchange capacity, improve the morphology regularity of type A molecular sieve, reduce the generation of impure crystals in type A molecular sieve, improve the perfection of the crystal structure of type A molecular sieve, and improve the adsorption performance of type A molecular sieve, the inventors found in the experimental process that when the sodium silicate solution and the sodium aluminate solution are mixed, the silicon-aluminum molar ratio is 1.6-2.0, especially the silicon-aluminum molar ratio is 1.8, the heating crystallization temperature is 90-100°C, and the heating crystallization time is 9-10h. The crystal structure of the type A molecular sieve obtained is highly perfect, the impure crystals are reduced, and the pore size of the obtained type A molecular sieve is larger, and the density distribution is uniform. Each spherical structure has good adsorption performance and can improve the calcium ion exchange capacity.

[0045] Beneficial Effects

[0046] 1. The preparation method provided by the present invention can improve the degree of perfection of the crystal structure of type A molecular sieve, improve the adsorption performance of type A molecular sieve, and increase the calcium ion exchange capacity.

[0047] 2. The preparation method provided by the present invention can reduce the generation of impurity crystals in the A-type molecular sieve and improve the adsorption performance of the A-type molecular sieve.

[0048] 3. The preparation method provided by the present invention can improve the morphological regularity of type A molecular sieve and increase the calcium ion exchange capacity.

[0049] 4. The preparation method provided by the present invention can increase the pore size of type A molecular sieve and improve the uniformity of its pore size distribution.

[0050] 5. The type A molecular sieve provided by the present invention can be better applied to the field of adsorption or separation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 : XRD spectra of type A molecular sieve provided in Examples 1-5.

[0052] Figure 2 : XRD spectra of type A molecular sieves provided in Examples 3 and 6-9.

[0053] Figure 3 : XRD spectra of type A molecular sieve provided in Example 3 and Examples 10-13.

[0054] Figure 4 : IR spectrum of type A molecular sieve provided in Example 1-5.

[0055] Figure 5 : IR spectra of type A molecular sieves provided in Examples 3 and 6-9.

[0056] Figure 6 : IR spectra of type A molecular sieve provided in Example 3 and Examples 10-13.

[0057] Figure 7 : Results of calcium ion exchange capacity testing of the type A molecular sieves provided in Examples 1-5.

[0058] Figure 8 : Results of calcium ion exchange capacity testing of the type A molecular sieves provided in Examples 3 and 6-9.

[0059] Fig. 9 : The calcium ion exchange capacity test results of the type A molecular sieve provided in Examples 3 and Examples 10-13.

[0060] Fig.10 : Graph showing the thermogravimetric test results of type A molecular sieve provided in Example 11.

[0061] Fig.11 : The type A molecular sieve provided in Example 11 was subjected to morphology testing to obtain test results. DETAILED DESCRIPTION

[0062] Example 1

[0063] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0064] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed evenly and placed in a muffle furnace for heating to 600 ° C. The mixture was calcined for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered with medium-speed filter paper to obtain a sodium aluminate solution;

[0065] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0066] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0067] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.4.

[0068] The temperature for heating and crystallization in S3 is 100°C.

[0069] The heating crystallization time in S3 is 8 hours.

[0070] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0071] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0072] Example 2

[0073] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0074] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0075] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0076] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0077] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.6.

[0078] The temperature for heating and crystallization in S3 is 100°C.

[0079] The heating crystallization time in S3 is 8 hours.

[0080] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0081] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0082] Example 3

[0083] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0084] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0085] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0086] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0087] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0088] The temperature for heating and crystallization in S3 is 100°C.

[0089] The heating crystallization time in S3 is 8 hours.

[0090] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0091] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0092] Example 4

[0093] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0094] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0095] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0096] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0097] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 2.0.

[0098] The temperature for heating and crystallization in S3 is 100°C.

[0099] The heating crystallization time in S3 is 8 hours.

[0100] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0101] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0102] Example 5

[0103] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0104] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0105] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0106] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0107] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 2.2.

[0108] The temperature for heating and crystallization in S3 is 100°C.

[0109] The heating crystallization time in S3 is 8 hours.

[0110] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0111] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0112] Example 6

[0113] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0114] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0115] S2. 6g of white carbon black and 6g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in water to obtain a sodium silicate solution;

[0116] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0117] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0118] The temperature for heating and crystallization in S3 is 80°C.

[0119] The heating crystallization time in S3 is 8 hours.

[0120] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0121] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0122] Example 7

[0123] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0124] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0125] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0126] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0127] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0128] The temperature for heating and crystallization in S3 is 90°C.

[0129] The heating crystallization time in S3 is 8 hours.

[0130] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0131] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0132] Example 8

[0133] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0134] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0135] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0136] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0137] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0138] The temperature for heating and crystallization in S3 is 110°C.

[0139] The heating crystallization time in S3 is 8 hours.

[0140] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0141] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0142] Example 9

[0143] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0144] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0145] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0146] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0147] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0148] The temperature for heating and crystallization in S3 is 120°C.

[0149] The heating crystallization time in S3 is 8 hours.

[0150] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0151] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0152] Example 10

[0153] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0154] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0155] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0156] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0157] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0158] The temperature for heating and crystallization in S3 is 100°C.

[0159] The heating crystallization time in S3 is 9 hours.

[0160] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0161] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0162] Embodiment 11

[0163] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0164] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0165] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0166] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0167] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0168] The temperature for heating and crystallization in S3 is 100°C.

[0169] The heating crystallization time in S3 is 10 hours.

[0170] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0171] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0172] Example 12

[0173] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0174] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0175] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0176] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0177] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0178] The temperature for heating and crystallization in S3 is 100°C.

[0179] The heating and crystallization time in S3 is 11 hours.

[0180] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0181] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0182] Example 13

[0183] The first aspect of this embodiment provides a method for preparing type A molecular sieve, comprising the following steps:

[0184] S1. 30 g of aluminum ash was added to 100 mL of deionized water, and washed with water at 40 ° C with continuous stirring for 2 h. After washing, the aluminum ash was filtered and dried to obtain desalted aluminum ash. 4.8 g of desalted aluminum ash and 9.6 g of sodium hydroxide were mixed and placed in a muffle furnace for heating to 600 ° C, and roasted for 120 min to obtain a treated product a, and the heating rate was 5 ° C / min; the treated product a was leached with 4 times the volume of deionized water, kept at 60 ° C for 30 min, and then filtered to obtain a sodium aluminate solution;

[0185] S2. 6 g of white carbon black and 8 g of sodium hydroxide were mixed to obtain a treated material b, and the treated material b was dissolved in 20 mL of water to obtain a sodium silicate solution;

[0186] S3. Mixing the sodium aluminate solution and the sodium silicate solution to obtain a mixture c, heating the mixture c for crystallization, washing, filtering, and drying to obtain a type A molecular sieve.

[0187] When the sodium silicate solution and the sodium aluminate solution in S3 are mixed, the silicon-to-aluminum molar ratio is 1.8.

[0188] The temperature for heating and crystallization in S3 is 100°C.

[0189] The heating crystallization time in S3 is 12 hours.

[0190] A second aspect of this embodiment provides a type A molecular sieve, which is prepared by the above-mentioned method for preparing the type A molecular sieve.

[0191] A third aspect of this embodiment provides an application of a type A molecular sieve, wherein the type A molecular sieve is applied in the field of adsorption or separation technology.

[0192] The aluminum ash used in the above embodiments 1-13 comes from Anhui Dongsheng Aluminum Technology Group Co., Ltd., with a purity of 45% to 50%. The main components include Al 48.22%, Cl 15.20%, S 9.96%, Ca 9.13%, Fe6.72%, Si3.80%, Mn 1.76%, Ba 1.16%, Zn 1.15% and other impurities 2.95%.

[0193] The white carbon black used in Examples 1-13 is sourced from Bengbu Vanke Silicon Materials, with a purity of 95%.

[0194] The silicon to aluminum molar ratio used in the present application is n(SiO2) / n(Al2O3).

[0195] Performance Testing

[0196] 1. XRD characterization test

[0197] The type A molecular sieve provided in Example 1-13 was tested by an X-ray diffractometer (XRD) to obtain an XRD spectrum. The XRD spectrum of the type A molecular sieve provided in Example 1-5 is shown in Figure 1 ; Example 3 and Example 6-9 provide A-type molecular sieve XRD spectra see Figure 2 ; Example 3 and Example 10-13 provide A-type molecular sieve XRD spectra see Figure 3 .

[0198] 2. FTIR characterization test

[0199] The type A molecular sieve provided in Example 1-13 was tested by Fourier transform infrared spectrometer (FTIR), its molecular skeleton was determined, and an IR spectrum was obtained. The IR spectrum of the type A molecular sieve provided in Example 1-5 is shown in Figure 4 ; Example 3 and Example 6-9 provide A-type molecular sieve IR spectra see Figure 5 ; Example 3 and Example 10-13 provide A-type molecular sieve IR spectra see Figure 6 .

[0200] 3. Determination of calcium ion exchange capacity

[0201] The calcium ion exchange capacity of the type A molecular sieve provided in Examples 1-13 was determined according to the method specified in QB / T 1768-2003; the results of the test on the type A molecular sieve provided in Examples 1-5 are shown in Figure 7 The results of testing the type A molecular sieves provided in Examples 3 and 6-9 are shown in Figure 8 The results of the tests on the type A molecular sieves provided in Examples 3 and 10-13 are shown in Fig. 9 .

[0202] The calcium exchange capacity E of type A molecular sieve is expressed in mg CaCO3 / g anhydrous zeolite, and the calculation formula is:

[0203]

[0204] In this experiment, C E represents the concentration of the EDTA standard titration solution (mol / L), V0 is the volume of the EDTA standard titration solution consumed in the blank titration (mL), and V E is the volume (mL) of the EDTA standard titration solution consumed in the sample titration, m is the mass (g) of the sample, and X is the measured ignition loss (%) of the A-type molecular sieve. Finally, the experimental results are expressed in the form of arithmetic mean and rounded to an integer. The national industry standard defines that the calcium ion exchange capacity is greater than 295mg CaCO3 / g as a qualified product.

[0205] 4. BET characterization test

[0206] The type A molecular sieve provided in Example 11 was tested using a specific surface area analyzer (BET) to obtain the surface and pore structure information of the type A molecular sieve. The test results are shown in Table 1.

[0207] 5. TG characterization test

[0208] The A-type molecular sieve provided in Example 11 was tested using a thermogravimetric analyzer (TG) to detect the thermal stability of the A-type molecular sieve and draw a thermogravimetric curve. The test results are shown in Fig.10 .

[0209] 6. Morphology test

[0210] The morphology of the type A molecular sieve provided in Example 11 was tested using a polarizing microscope to obtain the test results. Fig.11 .

[0211] In Examples 1 to 5, as the molar ratio of silicon to aluminum changes when sodium silicate solution and sodium aluminate solution are mixed during the preparation of type A molecular sieve, the Figure 1 It can be seen that the crystallinity and crystal structure of the obtained type A molecular sieve are also significantly affected. When the silicon-aluminum mole ratio is 1.4, it can be observed that the crystallinity of the type A molecular sieve is also at a low level, and the crystal structure of the type A molecular sieve is not perfect. With the gradual improvement of the silicon-aluminum mole ratio, the speed of its nucleus formation and the growth efficiency of the crystal during the preparation of the type A molecular sieve can be promoted. The inventor found in the experimental process that when the silicon-aluminum mole ratio increases from 1.4 to 1.8, the type A molecular sieve crystals begin to form, so that the type A molecular sieve has good adsorption performance.

[0212] Examples 3 and 6-9 provide type A molecular sieves obtained at different crystallization temperatures. Figure 2 It can be seen that a higher crystallization temperature will lead to an accelerated growth rate of molecular sieve crystals. When the crystallization temperature increases, the amorphous gel formed by mixture c will catalyze the formation of a sodium aluminosilicate anion skeleton; when the crystallization temperature is 80°C, the crystal structure is incomplete and the peak shape is unclear. When the crystallization temperature reaches 110°C, the crystallization speed will be too fast, and the crystal form of type A molecular sieve will change to produce impurity crystals.

[0213] Examples 3 and 10-13 provide type A molecular sieves obtained at different crystallization times; Figure 3It can be seen that the crystallization time will affect the morphology regularity of type A molecular sieve. The possible reason is that the increase in crystallization time prolongs the reaction time, which will lead to a decrease in the particle size of the molecular sieve, and too long a reaction time is not conducive to the formation of type A molecular sieves with good dispersion and regular morphology. When the crystallization time is 8h, the crystallization is insufficient, the grains are small, and the crystal structure of the obtained type A molecular sieve is incomplete and not fully formed. Complete crystals will be obtained when the crystallization time is 10h, but when the crystallization time reaches 11h, the structure of the molecular sieve crystals will change again and gradually transition to a stable state, that is, the crystals aggregate with each other to form impurity crystals. Figure 3 It can be seen that the phase and structure are clearest when the crystallization time is 9h and 10h.

[0214] pass Figure 4 It can be seen that at 1121cm -1 At 800cm, an asymmetric stretching vibration of a Si-O-Si bond can be observed. This characteristic peak is an important representation of the Si-O-Si network structure in silicate materials, from which the strength and stability of the silicon-oxygen bond in the sample can be analyzed. -1 At 456cm, it is the bending vibration peak of Si-O bond, which also reflects the vibration characteristics of silicon-oxygen bond in silicate materials. -1 The absorption peak at 800cm -1 The Si-O bond bending vibration peaks at , together indicate the formation of two tetrahedra of AlO4 and SiO4, which are common structural units in silicate and aluminate materials; Figure 4 It can be seen that in Examples 1 to 5, as the silicon-aluminum molar ratio of the sodium silicate solution and the sodium aluminate solution are mixed during the preparation of the type A molecular sieve, after the silicon-aluminum molar ratio reaches 1.8, other vibration peaks appear in the type A molecular sieve and transform to the type X molecular sieve. When the silicon-aluminum molar ratio reaches 2.2, the skeleton of the type A molecular sieve changes and the peak shape changes significantly. It can be seen that when the silicon-aluminum molar ratio reaches 2.2, it is not conducive to the synthesis of the type A molecular sieve.

[0215] Examples 3 and 6-9 provide type A molecular sieves obtained at different crystallization temperatures. Figure 5 It can be seen that when the crystallization temperature exceeds 100°C or is lower than 90°C, the peak shape of the obtained type A molecular sieve is not obvious. When the crystallization temperature is 100°C, the peak shape of type A molecular sieve is clear and the skeleton grows well.

[0216] Examples 3 and 10-13 provide type A molecular sieves obtained at different crystallization times; Figure 6It can be seen that when the crystallization time is 8h, the peak shape of type A molecular sieve is disordered, its crystal form has not yet formed, and the structure is unstable; when the crystallization time is 9-10h, the type A molecular sieve obtained can obtain a complete crystal nucleus, and its vibration peak gradually appears.

[0217] In Examples 1 to 5, as the molar ratio of silicon to aluminum changes when sodium silicate solution and sodium aluminate solution are mixed during the preparation of type A molecular sieve, the Figure 7 It can be seen that the calcium ion exchange capacity of type A molecular sieve increases first and then decreases with the increase of silicon-aluminum ratio; when the silicon-aluminum ratio gradually increases, the calcium ion exchange capacity of type A molecular sieve also increases, until it reaches a peak value when the silicon-aluminum ratio is 1.8. Thereafter, with the further increase of silicon-aluminum molar ratio, the calcium ion exchange capacity begins to show a downward trend. When the silicon-aluminum molar ratio exceeds 2, the growth rate of the crystal begins to exceed the nucleation rate, resulting in an increase in the crystal volume, and the structure of type A molecular sieve gradually changes, resulting in the molecular sieve's adsorption capacity for calcium ions weakened to below 325, which in turn causes a decrease in the calcium ion exchange capacity.

[0218] Examples 3 and 6-9 provide type A molecular sieves obtained at different crystallization temperatures. Figure 8 It can be seen that when the crystallization temperature exceeds 110°C, the adsorption capacity of the molecular sieve for calcium ions weakens to below 325. The possible reason is the twinning phenomenon caused by agglomeration between crystals during the crystallization process, which leads to the dissolution-recrystallization process of the molecular sieve, thereby affecting the crystallinity and morphology, and is accompanied by the formation of impurity crystals.

[0219] Examples 3 and 10-13 provide type A molecular sieves obtained at different crystallization times; Fig. 9 It can be seen that the calcium ion exchange capacity increases with the increase of crystallization time, but begins to decrease after a certain time. Because the crystallization time is insufficient, the crystallization is not complete, resulting in incomplete crystal development and the crystal nucleus has not yet formed. At this time, the molecular sieve structure is not complete, so the calcium ion exchange capacity is low. When the time reaches 10h, the calcium ion exchange capacity is the highest, indicating that the grains have grown to form 4A molecular sieve. However, if the crystallization time is too long, the specific regular cubic structure of the molecular sieve crystal will be expressed, and it will be irregular in shape, which is easy to produce impurity crystals. Combined with the XRD and IR analysis of the sample, it is concluded that the optimal crystallization time is 10h.

[0220] pass Fig.10It can be seen that the A-type molecular sieve begins to lose weight as the temperature rises. Before 200°C, the weight loss rate of the A-type molecular sieve is fast, mainly due to the evaporation of water and gas; at 200-800°C, the weight of the molecular sieve steadily decreases, and the free and physically adsorbed water in the pores of the molecular sieve is lost. When the temperature reaches 800°C, the weight loss rate of the molecular sieve gradually slows down. It can be seen that the porosity or pore volume of the A-type molecular sieve, the more the weight of the synthetic product decreases, the larger the porosity or pore volume, the relatively smooth material pores and fewer impurities.

[0221] pass Fig.11 It can be seen that the pore size of the type A molecular sieve provided in Example 11 is relatively large and the density distribution is uniform. Each pore has a clear spherical structure, indicating that the type A molecular sieve has a regular pore system.

[0222] Table 1

[0223]

Claims

1. A method for preparing type A molecular sieve, characterized in that: The following steps are involved: S1. The aluminum ash and the alkaline compound are mixed and then heated to obtain a treated product a; S2. The white carbon black and the alkaline compound are mixed to obtain a treated material b; S3. The treated material a and the treated material b are mixed to obtain a mixture c, and the mixture c is heated for crystallization, washed, filtered, and dried to obtain a type A molecular sieve; The treated product a and the treated product b are mixed with water respectively and then mixed to obtain a mixture c.

2. The method for preparing type A molecular sieve according to claim 1, characterized in that: In S1, the aluminum ash is first washed with water to obtain desalted aluminum ash.

3. The method for preparing type A molecular sieve according to claim 2, characterized in that: The mass ratio of desalted aluminum ash to alkaline compounds in S1 is 1:(1.5-2.5).

4. The method for preparing type A molecular sieve according to claim 2, characterized in that: The desalted aluminum ash and the alkaline compound in S1 are mixed, heated to 600° C., and calcined for 100-150 minutes to obtain a treated product a.

5. The method for preparing type A molecular sieve according to any one of claims 1 to 4, characterized in that: When the treated material b and the treated material a are mixed in S3, the silicon-aluminum molar ratio is 1.6-2.

0.

6. The method for preparing type A molecular sieve according to claim 5, characterized in that: When the treated material b and the treated material a are mixed in S3, the silicon-aluminum molar ratio is 1.8-2.

0.

7. The method for preparing type A molecular sieve according to claim 1, characterized in that: The temperature of the heating crystallization in S3 is 90-100°C.

8. The method for preparing type A molecular sieve according to claim 1, characterized in that: The heating crystallization time in S3 is 9-10 hours.

9. A type A molecular sieve, characterized in that: The molecular sieve is prepared by the method for preparing the type A molecular sieve according to any one of claims 1 to 8.

10. An application of the type A molecular sieve as claimed in claim 9, characterized in that: The A-type molecular sieve is used in the field of adsorption or separation technology.